ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENGELOLAAN BARANG MILIK DAERAH PADA OPD DI LINGKUNGAN PEMERINTAH KABUPATEN WAROPEN DENGAN KOMITMEN PIMPINAN SEBAGAI VARIABEL MODERATING - Belo, Berlian Ritha; Asnawi, Meinarni; Wijaya, Anthonius H.C. (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This study aims to examine the factors that influence the Quality of Regional Property Management in the Waropen District Government. These factors include the variable Quality of Regional Apparatus, Regulatory Compliance and Management Information Systems. In addition, this studyuses moderating variables, namely Leadership Commitment. The analytical tool in this study used WarpPLS 6.0. This software can analyze SEM models based on variants or better known as Partial Least Square. The SEM analysis model with WarpPLS can identify and estimate the relationship between latent variables whether the relationship is linear or non linear The results of this study indicate that Apparatus Quality and Regulatory Compliance affect the Management of BMD with P-values of each variable 0.028 and 0.005. While the management information system has no effect with a P-value of 0.148. In addition, the leadership commitment is not able to moderate the quality of regional apparatus to the quality of BMD management with a pvalue of 0.070. While organizational commitment is able to moderate the variable compliance with regulations and management information systems on the quality of BMD management with the respective P-value values of 0.001 and 0.012.